Associations between physical activity and eating‐disorder psychopathology among individuals categorised with binge‐eating disorder and bulimia nervosa. Issue 11 (11th September 2019) - Kerrigan, Stephanie G.; Lydecker, Janet A.; Grilo, Carlos M.
Abstract: Objective: While physical activity (PA) is known to have positive effects on psychological and physical health, little is understood about the association between non‐compensatory PA (ie, not compulsive or intended to control weight or shape) and psychopathology among individuals with eating‐disorder features. The present study explored associations between non‐compensatory PA and psychopathology among adults categorised with bulimia nervosa (BN) and binge‐eating disorder (BED). We further explored the association between compensatory PA and psychopathology among those who engaged in that form of "purging." Method: Participants were recruited through Mechanical Turk, an online recruitment platform. Individuals categorised with core features of BED (N = 138) and BN (N = 138) completed measures of eating‐disorder psychopathology (Eating Disorder Examination – Questionnaire [EDE‐Q] and Questionnaire on Eating and Weight Patterns – 5), depression (Patient Health Questionnaire – 2) and PA (both non‐compensatory and compensatory, measured using the EDE‐Q and Godin Leisure‐Time Exercise Questionnaire). Results: Engagement in non‐compensatory PA was associated with lower frequency of binge‐eating episodes, lower overvaluation of shape/weight and lower dissatisfaction with shape/weight ( P s < .05). Engagement in compensatory PA was related to greater frequency of binge‐eating episodes and greater restraint ( P s < .05). Discussion: Non‐compensatory PA was associated with lower eating‐disorder psychopathology. This suggests that PA is an important, though understudied, health behaviour among persons with features of BED and BN. Future research should examine the potential role of non‐compensatory PA in interventions for individuals with core features of these eating disorders.